Pengaruh Gaya Kepemimpinan, Disiplin Dan Motivasi Kerja Terhadap Kinerja Pegawai Dinas Perhubungan Provinsi Sumatera Barat - Shiva Audina; Khairil Aswan (Universitas 45 Surabaya, 2023)
This study aims to analyze the influence of leadership style (X1), discipline (X2) and work motivation on employee performance (Y) case study of the Department of Transportation of West Sumatra Province. The population in this study were all employees at the West Sumatra Province Transportation Service. Samples were taken and selected using saturated sampling with a total of 92 respondents. To answer this research the analysis used is regression analysis. This study shows that discipline over attendance, responsibility, attitudes and norms has a significant influence on employee performance at the West Sumatra Province Transportation Service.